Swimming and Bathing in Czechoslovakia until 1938 - Petra Tomšová (Jan Długosz University in Częstochowa, 2019)
Swimming and bathing in Czechoslovakia started to take shape at the beginning of the 19th century. At first, suitable locations in nature were used, with the first swimming baths built later on, primarily on rivers. The first competitive swimming races were held in 1845 on the Vltava River and in 1890, the AC Prague Sports Club founded a swimming department which also included competitive swimming races. In 1914, the Czech Union of Swimming was founded and in 1919 it was renamed as the Czechoslovak Amateur Swimming Association. The number of swimming pools at this time was very low, the conditions of Czechoslovak swimmers were not ideal, and their results at international swimming competitions suffered as a result.